Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.15252/embj.2021108293
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear cGAS: guard or prisoner?

Abstract: cGAS, an innate immune sensor of cellular stress, recognizes double‐stranded DNA mislocalized in the cytosol upon infection, mitochondrial stress, DNA damage, or malignancy. Early models suggested that cytosolic localization of cGAS prevents autoreactivity to nuclear and mitochondrial self‐DNA, but this paradigm has shifted in light of recent findings of cGAS as a predominantly nuclear protein tightly bound to chromatin. This has raised the question how nuclear cGAS is kept inactive while being surrounded by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 91 publications
(135 reference statements)
1
34
0
Order By: Relevance
“…Thus, effective safeguard mechanisms are key to avoid uncontrolled activation. cGAS is expressed in the cytosol and in the nucleus ( 10 , 11 ). Sensor functions of cGAS in the nucleus are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, effective safeguard mechanisms are key to avoid uncontrolled activation. cGAS is expressed in the cytosol and in the nucleus ( 10 , 11 ). Sensor functions of cGAS in the nucleus are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Most nuclear cGAS is tightly tethered to nucleosomes, by binding to the acidic patch formed by nucleosomal core histones and is thereby kept inactive (reviewed in ( 10 , 11 ). Chromatin structure, nuclear proteins competing with cGAS for the histone acidic patch or DNA, cofactors required for DNA binding, and posttranslational modifications of histones or cGAS, all contribute to regulation of nuclear cGAS DNA sensing ( 11 ). Disturbance of histone stoichiometry can result in pathogenic activation of nuclear cGAS by chromosomal DNA ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies began to note localization of cGAS to the nucleus and micronuclei cGAS hinting at non-canonical/STING-independent functions of cGAS that exist outside of its role as a cytoplasmic DNA sensor [ 98 , 99 , 100 , 101 , 102 , 103 , 104 ]. Liu et al demonstrated that upon exposure of cell lines to genotoxic stressors, there was robust nuclear translocation of cGAS even in the context of an intact nuclear membrane [ 100 ].…”
Section: Sting-independent Nuclear Functions Of Cgasmentioning
confidence: 99%
“…RIG-I senses blunt-end dsRNA based on the presence or absence of 5’modifications, while MDA5 requires dsRNA stem structures of so far unknown minimal length (Ablasser and Hur, 2020). The enzyme cGAS senses nucleosome-free dsDNA inside of cells and produces the second messenger 2’3’cGAMP, a direct ligand for the cyclic-di-nucleotide sensor STING (de Oliveira Mann and Hopfner, 2021). Nucleosome-free dsDNA has been shown to accumulate in cells after DNA damage and therefore DNA damage has been identified as a primary pathogenic event in an increasing number of sterile inflammatory conditions that are driven by cGAS/STING-dependent cytokine production (Crow and Stetson, 2021).…”
Section: Introductionmentioning
confidence: 99%